Völkisch writers and National Socialism : a study of right-wing political culture in Germany, 1890-1960 - Tourlamain, Guy (2014)
This book provides a view of literary life under the Nazis, highlighting the ambiguities, rivalries and conflicts that determined the cultural climate of that period and beyond. Focusing on a group of writers - in particular, Hans Grimm, Erwin Guido Kolbenheyer, Wilhelm Schaefer, Emil Strauss, Boerries Freiherr von Muenchhausen and Rudolf Binding - it examines the continuities in voelkisch-nationalist thought in Germany from c. 1890 into the post-war period and the ways in which voelkisch-nationalists identified themselves in opposition to four successive German regimes: the Kaiserreich, the W.